Factors influencing customers loyalty Towards Islamic banking: a case study in Gombak, Selangor / Farhan Lukman Rahman ... [et al.] - Lukman Rahman, Farhan; Wan Zakaria, Wan Mohd Farid; Wan Ibrahim, Wan Muhd Faez; Tuan Azam, Syed Khusairi; Musa, Mohd Hafizan (Universiti Teknologi MARA, Perlis, 2020)
The Islamic banking system governs two (2) basic principles which are mutual sharing of profit or loss and the prohibition of the collection and payment of interest. These basic principles are important to the establishment of an Islamic bank. Islamic law prohibits any activities that involve interest, gambling and speculative. Having great competition with foreign and conventional bank, Islamic banking industry needs variety of services and products to be offered to attract customers which is in compliance with shariah law. Thus, the main objective of this study is to examine the factors that influence customer’s loyalty towards Islamic banking. The independent variables include shariah compliant, product quality, service quality, and convenience. This study is conducted using structured questionnaire and were personally administrated across 303 respondents in Gombak, Selangor. This study is significantly important for the industry to find out the explanations and motive of customer’s loyalty in Islamic banks. Eventually, it will help the industry to establish a better services and products for the customers